Training of Small Farmers and Minority Agroforestry Landowners in Southeastern US – an Evolving Model - Christian, Colmore; Fraser, Rory; Herbert, Berneece S.; Scott, Chelsea (Advances in Social Sciences Research Journal, 2022)
Traditionally, extension activities are aimed at the transferal of knowledge from professionals to small-farmers and landowners. This process is supported by the Forestry Extension Model (FEM), which posit that professionals know what small-farmers and landowners need to learn, are the most credible source of land management information, and that small-farmers’/landowners’ education leads to sustainable land management practices. Although recent studies have supported a shift to peer-to-peer landowner education, there is still a need for initial professional-to-small-farmer/landowner training. Many underserved landowners lack forestry knowledge and practice and are usually unfamiliar with the available federal and state programs and resources. Therefore, they would require training before mentoring fellow small-farmers/landowners and gaining access to available resources. This paper, based in part on the results of a questionnaire survey and small-famers/landowners training initiatives, outlines elements of an evolving ‘landowners training model’ – a model where aspects of the FEM have been applied in a setting conducive to peer-to-peer mentoring.